In memoriam: Mohamed Said Abdullah - Twahir, Ahmed (African Journal of Nephrology, 2020)
Professor Mohamed Said Abdullah, a pioneer of Kenyan and African nephrology, died on 28 May 2020 at the age of 76. A teacher, father and friend to many in the nephrology community, to me he was always Dr Abdullah, my mentor.